The devil's daughter : a novel - Steel, Danielle (Delacorte Press, 2026)
"Graduating magna cum laude from MIT is the happiest day of Billie Banks's life, although her family is not part of it. Her mother, who always supported her, died when Billie was seventeen. Since then, her father has been slowly drinking himself to death on the family farm in Iowa, and she and her younger sister, Mickie, have grown even more estranged. Growing up, the siblings could not have been more different. Billie was shy, small, bookish, more like their mother; tall, blond Mickie was boldly sexual, craving attention, and lacking empathy for anyone, like their father. Despite Billie's attempts to look after Mickie following their mother's death, her sister consistently treated her with cruelty. So when Mickie invites Billie to move in with her in Los Angeles, Billie is both wary and hopeful. Taking a leap of faith, she joins her sister on the West Coast. While Mickie lands a questionable modeling job and falls in with a fast crowd, Billie begins working at a pathology lab and starts dating a warm, supportive reporter at the Los Angeles Times. But then the siblings' difficult history once again rises to the surface. This gripping story of a sisterly bond strained to the breaking point by narcissism and temptation is an unforgettable tale of good and evil from Danielle Steel"--